Students’ critical-metacognition activity based on their personality type - L D Fitriana; Y Fuad (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Metacognition and critical thinking become a foundation key to solve any problem. Therefore, students with higher level of those aspects tend to demonstrate better skills in accomplishing problem solving tasks. This study aims to describe student’s critical-metacognition activity in solving geometry problem based on Keirsey personality types, namely rational, idealist, guardian, and artisan. The samples were 8th grade students of the Labschool Universitas Negeri Surabaya. Students were given mathematics test and the adapted Keirsey personality questionnaires. Four volunteer students, with higher rank of mathematics and represented each Keirsey personality types, were selected as the research subjects. Data were collected by giving geometry task and interviews. The collected data were analyzed by using critical-metacognition indicators. The result affirms that all students demonstrated critical-metacognition through planning, monitoring, dan reflection activities although some parts were missed. For planning activity, rational and idealist students could explain their reason behind the strategy used. On the other hand, different condition was shown by guardian and artisan students who could not make conclusions correctly. For reflection activity, only guardian student who did not check his performance. This study suggests that teachers should facilitate students to practice critical thinking and metacognition activities in order to solve problems mathematically.